Theoretical framework construction on care complexity in Chinese hospitals: A grounded theory study - Bishan Huang; Hong Li; Meirong Chen; Na Lin; Zijuan Wang (Elsevier, 2019)
Objectives: This study aims to construct a theoretical framework to analyze risk factors and explore hospital nurses' perspectives on care complexity. Methods: The grounded theory method was adopted, and semi-structured in-depth interviews regarding the understanding of care complexity were conducted among the participants, including 31 nurses and nine doctors. In addition, data were coded and strictly analyzed in accordance with the coding strategy and requirements of grounded theory. Results: Our study reveals three factors that are closely related to care complexity, namely, (1) patient factors, including patients' condition, age, self-care abilities, compliance, social support systems, psychological conditions, expectations, and requirements; (2) nursing staff factors, including work experiences, education, knowledge and operational skills of caring, and communication skills; and (3) organization and equipment factors, including nursing workforce, nursing workload, support from multidisciplinary teams and ancillary departments, and the conditions of medical and hospital services. Conclusions: This study defines care complexity on the basis of its factors. Care complexity refers to the difficulty of nursing tasks during patient care plan implementation, which are affected by patients, nurses, and other factors in nursing and multisectoral, multidisciplinary cooperation. The framework can be beneficial for nursing education and for the improvement of the quality and efficiency of clinical nursing practice. Keywords: Care complexity, Nursing theory, Qualitative research, Root cause analysis